Studi Pengeringan Cabe dengan menggunakan Bath Drayer Bertenaga Listrik - Amanto, Bambang Sigit (Universitas Sebelas Maret, 2005)
Aims of this study is determine performance of drying chile that use electric energy. Type of dryer is bath dryer. Using of this study can be help farmers for to solve their problems in post harvest. This study use material and tools like (1) a set bath dryer with electric energy, (2) thermometer, (3) hygrometer, (4) oven, (5) balance, (6) chile and (7) others tool. The parameters in the study are temperatur (influence, material, dryer, out of material), relative humidity (influence, out of material), moisture content during drying with time intervals one hours and drying times. Depand on this experiment and discusions, can be conclusions that drying methode and making of dryer is easy, material for make dryer is easy to colect. Quality of final product is good, drying efficience is 22,36%, and final moisture content 7% dry base (drying time is 14 hours).